2020
DOI: 10.3390/ijms21249723
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of c-Peptide in Microvascular Complications of Type 1 Diabetes—Time for Translational Studies or Back to the Basics?

Abstract: People with type 1 diabetes have an increased risk of developing microvascular complications, which have a negative impact on the quality of life and reduce life expectancy. Numerous studies in animals with experimental diabetes show that c-peptide supplementation exerts beneficial effects on diabetes-induced damage in peripheral nerves and kidneys. There is substantial evidence that c-peptide counteracts the detrimental changes caused by hyperglycemia at the cellular level, such as decreased activation of end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Early clinical trials of C‐peptide supplementation showed some improvement in renal function of patients with type 1 diabetes, 65,66 but later trials reported only limited clinical benefit in terms of ameliorating microvascular disease‐induced complications (see Ryk et al. for a recent review 67 ). It is important, however, to consider the limitations of the clinical trials including the timing and duration of the treatment in relation to disease development.…”
Section: Discussionmentioning
confidence: 99%
“…Early clinical trials of C‐peptide supplementation showed some improvement in renal function of patients with type 1 diabetes, 65,66 but later trials reported only limited clinical benefit in terms of ameliorating microvascular disease‐induced complications (see Ryk et al. for a recent review 67 ). It is important, however, to consider the limitations of the clinical trials including the timing and duration of the treatment in relation to disease development.…”
Section: Discussionmentioning
confidence: 99%
“…Classically chronological age, age at T1D diagnosis, duration of T1D, average systolic blood pressure and HbA 1c are associated with chronic diabetic complications, but the relation of latter with residual β-cell function has been shown heterogenous results [4][5][6][7], besides there is great evidence that C-peptide counteracts the detrimental changes causes by hyperglycemia at the cellular level in animal studies [8].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors include unhealthy diet, old age, and sedentary lifestyle, playing essential roles in T2DM progression ( Lee et al, 2000 ). As depicted by a follow-up epidemiology of diabetes intervention and complication study, patients with diabetes who underwent standard insulin therapy show persistent slight inflammation and progressive vascular complications despite the intensified therapy afterward, indicating a potential metabolic memory signature prompted by hyperglycemia ( Ryk et al, 2020 ). However, the pathogenesis of this disease is complicated by genetic and environmental factors, which need further study.…”
Section: Introductionmentioning
confidence: 99%